PENGUNAAN EKSTRAK TOMAT SEBAGAI INOVASI PAKAN ALAMI UNTUK MENINGKATKAN KUALITAS WARNA IKAN BADUT MERAH MARUN (Amphiprion biaculeatus, Bloch 1790) - Sahusilawane, Helena Afia; Kilmanun, Juliana Ester; Beruatwarin, Tiara Marlina; Rahawarin, Jenni Paulin Loraene (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: Amphiprion biaculeatus, Bloch 1790 is one of the exported marine ornamental fish commodities. To meet export demand, must be from cultivation fish. However, the problem faced in cultivation conditions is that the color of the fish is not as attractive as in nature. This is due to uniform feeding. Therefore, alternative solutions are needed to enrich feed with natural pigment sources. One of them is red ripe tomato extract with high carotene content. Methods: The study used a completely randomized design with extract concentration treatments (0, 25%, 50%, 75%). Natural feed is made by coating, then applied to non-breeder sized fish obtained from BPBL Ambon. Extract efficiency parameters were measured through color characteristics, carotene content in the skin and fins, total length and body weight. The data obtained were analyzed using ANOVA and continued with the DMRT test at a significance level of 95%. Results: The results showed that tomato extract had a significant effect on color characteristics, carotenoid content, total length and body weight in maroon clownfish. The concentration of tomato extract which had the highest value for all parameters measured was in treatment 75% : 75 mL tomato extract + 10 mL binder + 15 g commercial feed). Conclusion: Tomato extract has the potential as a natural feed that can improve the color quality of A. biaculeatus with a usable concentration of 75%.